Keefektifan Pembelajaran Matematika dengan Model Pembelajaran REACT dan Model Kooperatif Tipe Jigsaw dalam Meningkatkan Hasil Belajar - Amsikan, Stanislaus; Bete, Julita Clarita; Salsinha, Cecilia Novianti (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2023)
This research aims to evaluate the effectiveness of mathematics learning using the REACT (Relating, Experiencing, Applying, Cooperating, and Transferring) learning model and the cooperative Jigsaw model in improving students’ learning outcomes. The learning models used are the REACT model and the cooperative Jigsaw model. This study utilizes a quasi-experimental method conducted at SMP IL Kapten Fatubaa. The research population includes all seventh-grade students at SMP IL Kapten Fatubaa, with the sample consisting of students from classes VIIA and VIIB. The research design used is the Posttest Only Control Group Design. Data is collected through tests and documentation, using instruments such as test questions and documentation. The results of data analysis using the independent t-test show that mathematics learning with the Jigsaw cooperative model and the REACT model are effective in improving students’ mathematics learning outcomes. Additionally, mathematics learning with the Jigsaw cooperative model is more effective than mathematics learning with the REACT model in enhancing students’ learning outcomes.